A novel cyclobutane-derived thiazole-thiourea hybrid with a potency against COVID-19 and tick-borne encephalitis: synthesis, characterization, and computational analysis - Omar, Rebaz Anwar; Koparir, Pelin; Koparir, Metin; Safin, Damir A. (Taylor & Francis Ltd, 2024)
In the present contribution, a novel cyclobutane-derived thiazole-thiourea hybrid 1-(4-(3-methyl-3-phenylcyclobutyl)thiazol-2-yl)-3-(p-tolyl)thiourea (1), which was readily fabricated from addition of p-isothiocyanatotoluene to 4-(3-methyl-3-phenylcyclobutyl) thiazol-2-amine, is reported. The formation of 1 was firmly confirmed by the means of elemental analysis, and IR and H-1 NMR spectroscopy. Theoretical DFT-based computations were additionally applied to reveal the structure and electronic features of the title compound. The chemical activity of 1 was estimated by the reactivity descriptors and MEP surface. ADMET properties of the reported compound were predicted in silico using online services. Potential inhibition of a series of the SARS-CoV-2 and tickborne encephalitis proteins by 1 was studied using molecular docking, which, in turn, allowed to reveal the ligand efficiency scores for the resulting protein-1 complexes. It was established that 1 exhibits the best inhibition activity against Nonstructural protein 14 (N7-MTase) and tick-borne encephalitis virus (TBEV) glycoprotein amongst the studied SARS-CoV-2 and TBE proteins, respectively.
Keywords: Cyclobutane; thiazole; thiourea; synthesis; computational study; molecular docking